Arthur And The YETI - Mercier,Johanne (london Phoenix Yard Books, 2013)
I'm Arthur and I'm seven, and last Saturday, at my grandparents' house, we all got a bit of a fright. The night before, the Neighbour heard strange noises coming from her garden and she saw two big, black eyes staring at her. Before we knew it, the whole had come to see the Yeti of Picket Lane.
Keywords: English story book